Urban Political Ecology.: Theoretical concepts, challenges, and suggested future directions - Zimmer, Anna (ERDKUNDE, 2010)
Political Ecology is a highly dynamic research field within geographical studies on development. Since Blaikie and Brookfield (1987) laid the foundations of the approach and formulated its first definition, the field has evolved in many different directions (among others, see Blaikie 1999). Only in recent years, however, have we seen a tendency, especially within Anglo-American geography, of applying political ecological concerns to other contexts than the traditionally rural ones: A still relatively new Urban Political Ecology has formed (Heynen et al. 2006). While it has brought into focus a whole range of new research objects, it has also used other concepts in a fruitful manner. Particularly promising is the concept of hybridity, which rejects the idea of any unnaturalness of the city. The entry point for investigations is the concept of metabolism, which allows asking classical questions of Political Ecology concerning power relations. Some theoretical and methodological challenges, however, remain for the further development of the field. Moreover, this article argues in favour of recognising diversified urban environments, of addressing the role of power relations in Urban Political Ecologies, and of including environmental imaginaries into the analysis.